2022
DOI: 10.1101/2022.01.05.475124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signaling modality within gp130 receptor enhances tissue regeneration

Abstract: Adult mammals are incapable of multi-tissue regeneration and augmentation of this potential may drastically shift current therapeutic paradigms. Here, we found that a common co-receptor of IL-6 cytokines, glycoprotein 130 (gp130), serves as a major nexus integrating various context-specific signaling inputs to either promote regenerative outcomes or aggravate disease progression. Via genetic and pharmacological experiments in vitro and in vivo, we demonstrated that a signaling tyrosine 814 (Y814) within gp130 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Treatments, including NSAIDs, opioids, corticosteroids, anxiolytics, muscle relaxants, antidepressants, and anticonvulsants (29) only mask the symptoms and do not treat the underlying cause. We have previously reported that a small molecule agent, R805, synthesized by our group can not only promote tissue regeneration, but also prevents articular cartilage degeneration in a rat model of PTOA (14). Strikingly, R805 inhibited inflammation in the joint, prevented articular cartilage degeneration, and mitigated pain and lameness in a posttraumatic joint injury dog model of OA (14).…”
Section: R805 Prevents Mandibular Condyle Destruction and Condylar Ca...mentioning
confidence: 90%
See 4 more Smart Citations
“…Treatments, including NSAIDs, opioids, corticosteroids, anxiolytics, muscle relaxants, antidepressants, and anticonvulsants (29) only mask the symptoms and do not treat the underlying cause. We have previously reported that a small molecule agent, R805, synthesized by our group can not only promote tissue regeneration, but also prevents articular cartilage degeneration in a rat model of PTOA (14). Strikingly, R805 inhibited inflammation in the joint, prevented articular cartilage degeneration, and mitigated pain and lameness in a posttraumatic joint injury dog model of OA (14).…”
Section: R805 Prevents Mandibular Condyle Destruction and Condylar Ca...mentioning
confidence: 90%
“…Our group has extensive surgical experience in successfully inducing OA in small and large animal models of degenerative joint disease (14,23,24). We have previously shown that partial meniscectomy in rats can induce OA formation in the knee joint (23).…”
Section: Establishing a Large Animal Model Of Tmj Ptoa In A Yucatan M...mentioning
confidence: 99%
See 3 more Smart Citations